Comparing of Flash Cards and Alphabet Puzzles for Children's Literacy and Learning Interest - Dewi Ratna Ningrum; Muhajir Muhajir; Sucipto Sucipto; Yuni Hanifah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study was conducted to evaluate the effectiveness of picture cards and alphabet puzzle media in improving early childhood literacy skills and increasing learning interest among children at TK ABA II Socah. The research involved 24 students in Group B, and all members of the population were selected as the sample through a saturated sampling technique. This study applied a quantitative approach by comparing the use of picture cards in the control group and alphabet puzzles in the experimental group. Data were analyzed using IBM SPSS through several statistical procedures, including tests of homogeneity, normality, instrument validity, and the Independent Samples T-test. These analyses were carried out to ensure that the data met the necessary assumptions and that the research instruments were valid and reliable for measuring both reading ability and learning interest. The results revealed a significant difference between the two groups. For reading ability, the significance value was 0.001, which is lower than 0.05, indicating that the difference between the groups was statistically significant. Similarly, for learning interest, the significance value was 0.000, which also confirms a significant difference. These findings demonstrate that the use of alphabet puzzle media produces better outcomes than picture cards in supporting early childhood learning. Children who learned through alphabet puzzles showed stronger reading performance and higher enthusiasm in participating in classroom activities. Therefore, this study concludes that alphabet puzzles are more effective than picture cards in enhancing literacy development and fostering students’ interest in learning at the early childhood education level.